ANALISIS IMPLIKATUR PERCAKAPAN TOKOH DALAM FILM MONSIEUR LAZHAR KARYA PHILIPPE FALARDEAU - Frina Carrina Tzaba, - (2019)
Implikatur percakapan merupakan pemerolehan maksud dalam sebuah tuturan yang tidak terdapat pada tuturan sehingga pemerolehan maksud disesuaikan dengan konteks yang terikat pada setiap maksim dalam prinsip kerja sama. Fokus penelitian ini berupa jenis implikatur percakapan yang dipengaruhi oleh maksim pada prinsip kerja sama dan ketidaktaannya dalam film Monsieur Lazhar karya Philippe Falardeau. Penelitian ini menggunakan desain penelitian kualitatif. Tujuan dalam penelitian ini adalah: 1) Menjelaskan jenis implikatur percakapan yang terdapat pada percakapan tokoh dalam film Monsieur Lazhar karya Philippe Falardeau; 2) Menjelaskan maksud dari jenis implikatur percakapan yang ditemukan pada percakapan tokoh dalam film Monsieur Lazhar karya Philippe Falardeau; dan 3) Mengkaji ketidaktaatan maksim pada prinsip kerjasama yang terjadi pada percakapan tokoh dalam film Monsieur Lazhar karya Philippe Falardeau. Subjek pada penelitian ini berupa tuturan pada percakapan tokoh dalam film Monsieur Lazhar serta objek berupa percakapan tokoh yang merupakan implikatur percakapan tokoh dalam film. Penelitian ini menggunakan metode simak, bebas, libat, dan cakap (SLBC) pada tahap pengumpulan data. Pada tahap analisis data menggunakan pilah unsur penentu (PUP) yang dilanjutkan dengan teknik hubungan banding menyamakan (HBS). Hasil penelitian implikatur percakapan tokoh dalam film Monsieur Lazhar menunjukkan terdapat 5 jenis implikatur percakapan umum dan 40 jenis implikatur percakapan khusus. Dalam penelitian ini, implikatur percakapan sering dipengaruhi oleh maksim cara sebanyak 19 tuturan dengan ketidaktaatan flouting of a maxim sejumlah 28. Penelitian ini memiliki implikasi dalam memberikan kontribusi secara informatif untuk memperkaya pengetahuan pragmatik khususnya tentang implikatur percakapan.;--This research explains the various types of conversational implicature in the utterance of the characters in the film Monsieur Lazhar by Philippe Falardeau. The implication of the conversation is the acquisition of meaning that is indirectly implied in an utterance so that the acquisition of meaning is determined by the context that is bound to each maxim in the principle of cooperation. The focus of this research is the type of conversational implicature, which is influenced by the maxim on the principle of cooperation and its violation in the film Monsieur Lazhar by Philippe Falardeau. This study uses a qualitative research design. The objectives of this study are: 1) to explain the types of conversational implicature in the conversation of the characters found in the film Monsieur Lazhar by Philippe Falardeau; 2) to explain the purpose of the type of conversational implicature found in the conversation of the characters in the film Monsieur Lazhar by Philippe Falardeau; and 3) to examine the violation of the principle of cooperation that occurs in the conversation of the characters in the film Monsieur Lazhar by Philippe Falardeau. The subject of this research is the utterance of the characters' conversations in the film Monsieur Lazhar, while the object of this research is the characters' conversation which includes conversation implicature in the film. This research uses the method of simak, bebas, libat and cakap (SLBC) for collecting the data. In analyzing the data, the research uses pilah unsur penentu (PUP) and hubungan banding menyamakan (HBS) technique as well. The results of the conversational implicature in Monsieur Lazhar's film show that there are five types of generalized conversational implicature and 40 particularized conversational implicature. Both types are influenced by the cooperative principle and the violation of maxims. In this research, there are no maxims of quantity and quality in the utterance of generalized conversational implicature. As for both utterance types, they do not have infringing a maxim. Particularized conversational implicature which is influenced by quantity maxim and flouting of a maxim is a form of conversational implicature that often appears in the film of Monsieur Lazhar. The implication of this research is to provide informative contributions in enriching pragmatic knowledge, especially about the implicature of conversation.